Non‐Point Source Pollution of Dissolved Phosphorus in the Ethiopian Highlands: The Awramba Watershed Near Lake Tana. Issue 6 (19th May 2016) - Moges, Mamaru A.; Tilahun, Seifu A.; Ayana, Essayas K.; Moges, Michael M.; Gabye, Nigus; Giri, Shree; Steenhuis, Tammo S.
Abstract : Intensifying agriculture in Africa is degrading the water quality of rivers and lakes, thereby, threatening the sustainable use of water resources. In Lake Tana in the Ethiopian highlands, the first signs of eutrophication were recently observed. Since relatively little is known about the non‐point source pollution in sub‐Saharan Africa, the objective was to examine non‐point sources phosphorus contribution of an agricultural watershed near Lake Tana. The 7‐km 2 Awramba watershed was selected. Dissolved phosphorus concentration (DPC) in groundwater and soil‐available phosphorus was measured at three landscape positions and discharge, sediment, and DPC at the outlet. The results indicated that DPC in groundwater was most elevated in the periodically saturated valley bottoms while available P was the greatest in the cropped fields at mid‐slope. The DPC increased with discharge. During base flow the concentration in the stream was similar to that in ground water. The results were consistent with other hydrological watershed studies in which the major source of runoff, erosion, and phosphorus originated from valley bottom lands. Hence, converting the periodically saturated areas in the stream corridor to buffer zones with reduced P input can be an important tool in reducing P from rural watersheds in the Ethiopian highlands. Abstract : Lake Tana in the Ethiopian highlands is showing the first signs of eutrophication. The origin of the non‐point source dissolved phosphorus loss is examined. The periodically saturated and reduced bottomlands are a main source of P. Maize grown mid‐slope provides only P during high flow events. Converting the bottom lands to buffer zones will decrease non‐point source pollution.